2019
DOI: 10.1109/access.2019.2910148
|View full text |Cite
|
Sign up to set email alerts
|

How Course, Contextual, and Technological Challenges are Associated With Instructors’ Individual Challenges to Successfully Implement E-Learning: A Developing Country Perspective

Abstract: Many universities and colleges in developing countries around the world have started using e-learning courses to keep up with the technological revolution of the higher education sector in the developed world. E-learning has served as a catalyst for higher education to expand in the last decade. However, there are still many challenges facing universities in the developing world, as they attempt to implement e-learning. This paper investigated the main challenges that could significantly impact the implementat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 58 publications
2
36
0
Order By: Relevance
“…All the data found from the analysis of seven themes portrayed the severe impact of COVID-19 on tertiary-level education in Bangladesh. Digitally advanced countries can provide effective online learning (Basilaia & Kvavadze, 2020), and developing countries with limited technical resources face many challenges in implementing online education (Aldowah et al, 2019). As a developing country, the scope of online education is still low in Bangladesh.…”
Section: Discussionmentioning
confidence: 99%
“…All the data found from the analysis of seven themes portrayed the severe impact of COVID-19 on tertiary-level education in Bangladesh. Digitally advanced countries can provide effective online learning (Basilaia & Kvavadze, 2020), and developing countries with limited technical resources face many challenges in implementing online education (Aldowah et al, 2019). As a developing country, the scope of online education is still low in Bangladesh.…”
Section: Discussionmentioning
confidence: 99%
“…In the e-learning literature, several studies found that the acceptance of e-learning systems in higher education might be influenced by different factors related to instructor characteristics, course quality, student awareness and information technology infrastructure [7], [17], [31]. The majority of recent studies have confirmed that instructors' characteristics are crucial for the success and acceptance of e-learning systems [47], [48]. In his study, Ghazal et al [47] found that the effect of instructor characteristics on students' usage and acceptance of e-learning is very important.…”
Section: Recent Studies On E-learning Acceptancementioning
confidence: 99%
“…Wright [17] found that course characteristics in terms of course design and course quality could significantly contribute to e-learning success. In another study conducted by Aldowah et al [48], the researchers indicated that course characteristics (course design and course content) may play a key role in shaping the learning process and, consequently, motivate students to use and accept an e-learning system. This motivated Ghazal et al [47] to study the effect of the factors related to course characteristics on learning management system (LMS) acceptance.…”
Section: Recent Studies On E-learning Acceptancementioning
confidence: 99%
“…Restricted levels of participation and engagement Restricted levels of participation and engagement and attitudes of both students and teachers in applying their knowledge and skills in an e-learning environment. E-learning competence is contextual (Aldowah et al, 2019;Freeze et al, 2019), and the technological knowledge and skills previously acquired may not be efficiently translated in the new learning environment and platform. The attitude towards e-learning between students and teachers was comparable, or complementary at best.…”
Section: Critical Reflections On E-learning Readinessmentioning
confidence: 99%